Profitability and Ownership Structure as Determinants of Financial Reporting Timeliness in Healthcare Companies Listed on the Indonesian Stock Exchange - Mediaty, Mediaty; Anto, Fitri Anto; Hamid Habbe, Abdul (Politeknik Siber Cerdika Internasional, 2024)
Background: Timeliness of financial reporting is a crucial indicator of financial reporting quality, as it affects the relevance and usefulness of information for stakeholders. In the healthcare sector, which has experienced significant growth, internal company factors such as profitability and ownership structure are assumed to influence the timeliness of financial reporting. Objective: This study aims to examine the effect of profitability and ownership structure on the timeliness of financial reporting in healthcare companies listed on the Indonesia Stock Exchange. Methods: This study employed a purposive sampling method, selecting 20 healthcare companies that were consistently listed on the Indonesia Stock Exchange during 2020. The data were analyzed using logistic regression with a significance level of 5%. Results: The results of hypothesis testing indicate that profitability has a significant effect on the timeliness of financial reporting. In contrast, ownership structure does not have a significant effect on the timeliness of corporate financial reporting. Conclusion: The findings demonstrate that profitability plays an important role in determining the timeliness of financial reporting in healthcare companies, while ownership structure does not significantly influence reporting timeliness. This suggests that financial performance is a more decisive factor than ownership characteristics in encouraging timely financial reporting.